MODERN METHODS OF MILK ANALYSIS - Planinić, Ana; Čelan, Stipe; Semren, Orjana; Pilić, Zora (International Journal of Research -GRANTHAALAYAH, 2022)
Milk is a product of the mammary gland obtained by proper and regular milking of healthy, properly fed cows, sheep, goats, without adding or taking anything away. This paper describes modern methods used for milk analysis and their working principle. 30 samples of raw milk were collectedas follows: 10 samples of cow, 10 samples of goat and 10 samples of sheep raw milk. The obtained results of raw milk quality parameters were processed, analyzed and compared with the maximum permissible concentrations prescribed by the Ordinance on raw milk.The work was written by the method of prospective study (experimental research). Milk testing was conducted during the period from 1 March 2020 to May 1, 2020.Samples were collected from primary producers of raw milk from the territory of Canton 10 in the manner prescribed by the Regulation on the method of sampling milk. They were transported and analysed in the Laboratory for Quality and Microbiology of Raw Milk - Department of Food and Veterinary Medicine of Canton 10.During this period, tests of raw milk were performed on the MilkoScan 7 device , a milk analyzer that works on the principle of close infrared spectroscopy with Fourier transform.